2011
DOI: 10.1136/gutjnl-2011-300715
|View full text |Cite
|
Sign up to set email alerts
|

Changes in prevalence, incidence and spontaneous loss of gastro-oesophageal reflux symptoms: a prospective population-based cohort study, the HUNT study

Abstract: Objective Changes in the occurrence of gastroesophageal reflux symptoms (GERS) in the population remain uncertain. This study aimed to determine the prevalence changes, the incidence, and the spontaneous loss of GERS.Design This population-based cohort study was conducted within the NordTrøndelag health study (the HUNT study), a longitudinal series of population-based health surveys in Nord-Trøndelag County, Norway. The study base encompassed all adult residents in the county, and the participants reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
3
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 115 publications
(114 citation statements)
references
References 25 publications
5
103
3
3
Order By: Relevance
“…In addition, GERS were assessed in a 'non-responder study' (Mini-Q) after HUNT 3 in 2009, where those who did not participate in HUNT 3 were invited. (2,16) The individuals who participated in HUNT 2 and were followed up in Mini-Q were also eligible for inclusion in the present study (figure 1).…”
Section: Study Population and Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, GERS were assessed in a 'non-responder study' (Mini-Q) after HUNT 3 in 2009, where those who did not participate in HUNT 3 were invited. (2,16) The individuals who participated in HUNT 2 and were followed up in Mini-Q were also eligible for inclusion in the present study (figure 1).…”
Section: Study Population and Designmentioning
confidence: 99%
“…Gastroesophageal reflux disease (GERD) is a highly prevalent disease in Western populations, (1,2) associated with a decreased health-related quality of life (3,4) and an increased risk of esophageal adenocarcinoma. (5,6) The Montreal definition and classification of GERD states that: "GERD is a condition which develops when the reflux of stomach contents causes troublesome symptoms and/or complications" and the definition recognizes that heartburn and acid regurgitation are characteristic symptoms of GERD.…”
Section: Introductionmentioning
confidence: 99%
“…(25) This suggests that the majority of those reporting severe GERS actually have GERD according to the Montreal definition and classification of GERD. (25,26,29) …”
Section: Assessment Of the Outcome Gastroesophageal Reflux Symptomsmentioning
confidence: 99%
“…An age-matched control population for evaluations of height, weight, waist-hip measurement, blood pressure, HDL, alanine aminotransferase (ALAT) and calcium was drawn from the third North-Trøndelag Health Study (HUNT) in 2006-2008, which included clinical investigations of 23 702 women and 12 966 men between 18 and 72 years of age (20). The Lunar database was used as reference for BMD and fat mass measurements; a previous study demonstrated that BMD in the femur and total body of the subjects in this database was comparable with the general Norwegian population (21).…”
Section: Subjects and Designmentioning
confidence: 99%